Analysis of Factors Influencing Seed Breeder’s Decisions to Certify Rice Seeds in North Sumatra Province, Indonesia - Widari, Tenni Sri; Chalil, Diana; Sidique, Shaufique F. (Agro Bali : Agricultural Journal, 2025)
The number of breeding rice seeds in North Sumatra Province is decreasing every year. This will have an impact on the availability of rice seeds for farmers. Meanwhile, a certification process is needed to produce quality rice seeds.  The aim of this research is to analyze how the differences in factors such as level of education, knowledge of certifying seeds, experience as a seed breeder, seed selling price, land area, and rice seed production costs can influence the seed breeder's decision to certify the rice seeds produced. The method used is the Average Difference Test with Analysis of Variance (ANOVA) Test with sample determination using saturated samples (census) totaling 44 seed breeder groups. The results of the analysis show that the variables of knowledge, experience, selling price, and production costs differ significantly for each decision taken by seed breeders in rice seed certification activities. While the variables of education level and land area are not significantly different, this is because the education level of the seed breeder group is almost the same, namely an average of high school / vocational high school graduates, while the area of land controlled by the seed breeder group is also not significantly different between the 3 groups, the average land area of the Non-Seed Certification group is 16.25 ha, the average land area of the Unfinished Seed Certification group is 17.42 ha, and the average land area for the Seed Certification group is 27.35 ha.